2013
DOI: 10.1080/08897077.2012.755146
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Detection Rates of Risky Marijuana Use in Colorado Health Care Settings

Abstract: Findings suggest that health care providers may be serving increasing numbers of patients using marijuana for medical or recreational purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The risk of dependence can be heightened when chronic use has a component of emotional relief, which is common among those applying for medical marijuana access (O'Connell & BouMatar 2007). The results are consistent with the findings of Richmond et al (2013) in which increases in overall marijuana use, and severity of use, coincided with increased numbers of medical marijuana users and dispensaries in Colorado. They are also consistent with findings of greater frequency of marijuana use among returning medical marijuana users in Michigan compared to first-time applicants for a medical marijuana card (Ilgen et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The risk of dependence can be heightened when chronic use has a component of emotional relief, which is common among those applying for medical marijuana access (O'Connell & BouMatar 2007). The results are consistent with the findings of Richmond et al (2013) in which increases in overall marijuana use, and severity of use, coincided with increased numbers of medical marijuana users and dispensaries in Colorado. They are also consistent with findings of greater frequency of marijuana use among returning medical marijuana users in Michigan compared to first-time applicants for a medical marijuana card (Ilgen et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Recent research has reported increased cannabis use by drivers in California from 2007 to 2010 (36) and increased marijuana use by patients treated in Colorado health care settings (37). The marked increase in the prevalence of cannabinol reported in the present study is likely germane to the growing decriminalization of marijuana.…”
Section: Discussionmentioning
confidence: 45%
“…Finally, due to the long half-life of THC, our outcome variable (cannabis positivity) does not directly measure cannabis impairment. THC metabolism follows the 3-compartment model of pharmacokinetics (Sempio et al 2020), and traces of its inactive metabolite, THC-COOH, can be found within the blood specimen up to a week after cannabis consumption whereas adverse effects of cannabis on driving usually disappear after 24 h (Ronen et al 2008;Richmond et al 2013). Since 94.6% of FARS toxicological cannabinoid testing data came from whole blood specimens, it is possible that a driver's positive toxicological testing data for cannabis may be due to an inactive drug metabolite (THC-COOH) from past use, and not necessarily represent current impairment.…”
Section: Limitationsmentioning
confidence: 99%